Maternal and perinatal outcomes in women planning vaginal birth after caesarean (VBAC) at home in England: secondary analysis of the Birthplace national prospective cohort study. (23rd July 2015) - Rowe, R; Li, Y; Knight, M; Brocklehurst, P; Hollowell, J
Abstract : Objective: To compare vaginal birth rates in women planning vaginal birth after caesarean (VBAC) at home versus in an obstetric unit (OU) and explore transfer rates in women planning home VBAC. Design: Prospective cohort study. Setting: OUs and planned home births in England. Population: 1436 women planning VBAC in the Birthplace cohort, including 209 planning home VBAC. Methods: We used Poisson regression to calculate relative risks adjusted for maternal characteristics. Main outcome measures: Main outcomes: (i) vaginal birth and (ii) transfer from planned home birth to OU during labour or immediately after birth. Secondary outcomes: (i) composite of maternal blood transfusion or admission to higher level care, (ii) stillbirth or Apgar score <7 at 5 minutes, (iii) neonatal unit admission. Results: Planned VBAC at home was associated with a statistically significant increase in the chances of having a vaginal birth compared with planned VBAC in an OU (adjusted relative risk 1.15, 95% confidence interval 1.06–1.24). The risk of an adverse maternal outcome was around 2–3% in both settings, with a similar risk of an adverse neonatal outcome. Transfer rates were high (37%) and varied markedly by parity (para 1, 56.7% versus para 2+, 24.6%). Conclusion: Women in the cohort who planned VBAC at home had an increased chance of a vaginal birth compared with those planning VBAC in an OU, but transfer rates were high, particularly for women with only one previous birth, and the risk of an adverse maternal or perinatal outcome was around 2–3%. No change in guidance can be recommended. Tweetable abstract: Higher vaginal birth rates in planned VBAC at home versus in OU but 2–3% adverse outcomes and high transfer rate. Tweetable abstract: Higher vaginal birth rates in planned VBAC at home versus in OU but 2–3% adverse outcomes and high transfer rate.